Perception or Reality, What Matters Most When it Comes to Crime in Your Neighbourhood? - Manning, M; Ambrey, C; Fleming, C (My University, 2013)
Public perceptions of crime and victimisation can influence an individual’s subjective well-being. Research into the impact of the fear of crime and victimisation on subjective well-being, however, has been limited; particularly with respect to the relative contributions of real versus perceived crime towards an individual’s self-reported life satisfaction. Improving our understanding of the relationship between crime and well-being is important, as public resources assigned to reducing or controlling crime could be assigned to addressing other social concerns. This paper extends the literature by exploring the contribution of real and perceived crime in an individual’s local area to their self-reported life satisfaction. Our results indicate that: (1) individuals’ perceptions of crime in their local area are far greater than actual levels of crime; (2) the gap between perceived and real crime is widening as real crime rates fall faster than the perceived rate of crime; (3) real crime rates detract more from an individual’s self-reported life satisfaction than perceived rates of crime; however, (4) perceived rates of crime have an adverse impact on life satisfaction beyond those associated with real crime; and (5) there is significant heterogeneity in the life satisfaction effects of real and perceived crime among groups of individuals. These results, together with empirical evidence highlighting successful strategies for moderating perceptions of crime, facilitate the development of more informed public policy that will improve individual life satisfaction and, ultimately, community well-being.
Social Indicators Research
Keywords: Health -- Wellbeing; Life Events -- Crime; Life Events -- Resilience and Adversity; Satisfaction -- Life; Disadvantage, adversity and resilience; Health and wellbeing; Life Events; Satisfaction; Health; Wellbeing; Life; Resilience and Adversity; Crime; Dsiadvantage, adversity and resilience; Adversity and resilience; Health and wellbeing